Elementos para a estruturação do diálogo entre jurisdição estatal e arbitral - Nery, Maria Carolina (2019)
This paper aims to analyze the nature of arbitration in Brasil, and its jurisdictional character. From the understanding of the Kompetenz-Kompetenz principle and its true context in the Brazilian legal system, we clarify that there is no hierarchy between the Judiciary and the Arbitration Panel, neither control of the arbitrators’ activities during the arbitration. Some situations, in an illustrative manner, are then presented, in which there can be interaction between the Judiciary and the Arbitration Panel, always within the limits drawn by the law